ANALISIS EFISIENSI PADA GENERATOR 12 SLOT 8 POLE - Ayu Martha Lestari; Jatisukamto Gaguk; Muttaqin Zainul Aris (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2018)
Wind energy can be used as an electric energy generator, known as a Bayu Power Plant (PLTB). The PLTB component consists of wind turbines, generators, and batteries. The efficiency of the generator is influenced by the loading system on the power plant, which includes the use of data logger and controller components. The study aimed to find out the efficiency of the 12 Slot 8 Pole generator. The research method uses a MagNet Software simulation, with variables: in the form of R = 15 resistance and rotor rotation n = 1000 - 10,000 rpm. The results of the study show that the efficiency of the generator and the circuit starts to stabilize at rotor rotation n = 3000 rpm; highest efficiency when rotor rotation n = 9000 rpm with efficiency ηmax = 90,04614%; average efficiency ηav = 88.867%. Keywords: PLTB, 12 Slot 8 Pole Generator, MagNet Software, efficiency.